2019
DOI: 10.1093/pasj/psz025
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectra of Sagittarius A East and diffuse X-ray background near the Galactic center

Abstract: This paper reports the analysis procedure and results of simultaneous spectral fits of the Suzaku archive data for Sagittarius (Sgr) A East and the nearby Galactic center X-ray emission (GCXE). The results are that the mixed-morphology supernova remnant Sgr A East has a recombining plasma (RP) with Cr and Mn Heα lines, and a power-law component (PL) with an Fe I Kα line. The nearby GCXE has a ∼1.5-times larger surface brightness than the mean GCXE far from Sgr A East, although the spectral shape is almost iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
3
11
1
Order By: Relevance
“…Our best-fit temperatures are similar to that from the XMM-Newton study by Sakano et al (2004), which also suggests low abundances of S, Ar, and Ca (Z/Z e =1-3). We found larger differences between our Chandra results and the Suzaku results by Ono et al (2019), which requires two recombining plasma models with different IGE abundances. This large discrepancy is likely caused by the different spectral extraction regions.…”
Section: Two-temperature Modelcontrasting
confidence: 79%
See 4 more Smart Citations
“…Our best-fit temperatures are similar to that from the XMM-Newton study by Sakano et al (2004), which also suggests low abundances of S, Ar, and Ca (Z/Z e =1-3). We found larger differences between our Chandra results and the Suzaku results by Ono et al (2019), which requires two recombining plasma models with different IGE abundances. This large discrepancy is likely caused by the different spectral extraction regions.…”
Section: Two-temperature Modelcontrasting
confidence: 79%
“…A two-temperature component is needed to fit the spectrum in the 2-8 keV band, as pointed out in previous studies (Sakano et al 2004;Park et al 2005;Koyama et al 2007;Ono et al 2019). We found that an absorbed two-temperature plasma model vvapec+vvapec with abundances tied together well describes the spectrum in the 2-8 keV band and provides a reduced χ 2 (c n 2 ) of 1.45 (dof=381).…”
Section: Two-temperature Modelsupporting
confidence: 70%
See 3 more Smart Citations